The Nanosyntax of Spatial Deixis1. (30th September 2016) - Lander, Eric; Haegeman, Liliane
Abstract: This paper provides a fine‐grained morphosyntactic analysis of spatial deixis. We propose that the universal core of spatial deixis is a three‐way contrast: Proximal 'close to speaker', Medial 'close to hearer', and Distal 'far from speaker and hearer'. This system arises from three features merged as heads in a single universal functional sequence: Dx3 > Dx2 > Dx1 . The hierarchy is understood in terms of superset‐subset relations, such that Proximal [Dx1 ] is a subset of Medial [Dx2 [Dx1 ]], which in turn is a subset of Distal [Dx3 [Dx2 [Dx1 ]]]. Evidence comes from patterns of syncretism and morphological containment in the demonstrative systems of a number of genetically diverse languages. Regarding syncretisms, languages can show a transparent three‐way morphological contrast, or some sort of syncretism: Medial/Proximal vs. Distal, Distal/Medial vs. Proximal, or a totally syncretic Distal/Medial/Proximal (i.e. a neutral demonstrative). These syncretisms entail that the features responsible for the Proximal and Medial readings be adjacent and that the features responsible for the Distal and Medial readings be adjacent in the fseq. Regarding containment, we show that Proximal can be structurally contained within Medial and that Medial can be structurally contained within Distal, meaning that Medial structures are larger than Proximal structures, and that Distal structures are larger than Medial structures, confirming our hierarchy. We show that these facts are naturally accounted for by nanosyntactic principles of spellout. We end the paper by accounting for potential counterexamples and other issues.